남북한 농림산물 계약재배 추진방안 연구 - 권태진 (한국농촌경제연구원, 2009)
Over the past 20 years, inter-Korean cooperation has developed. The trade volume of goods has significantly increased and the contents of economic cooperation has diversified. Nevertheless, many people expect more active trade and cooperation. They want to explore new directions for co-existence and co-prosperity between the South and the North. One of the ways is contract farming. Contract farming is an agreement between legally independent firms or farmers for the production of a commodity for a future market. However, the agreement on institutional measures between the two Koreas is necessary in order to promote contract farming. Besides the institutional aspects, establishment of operating measures, the selection of the target crops, and troubleshooting on import process are required. This research aims to provide ways and policy issues for contract farming of agricultural and forestry products between two Koreas. We have pursued to find effective measures and policies to promote agricultural contract farming. In this study, we assumed that the North is on the producer's position, the South is on the buyer's position.